HUBUNGAN ANTARA PERSEPSI DUKUNGAN KELUARGA SEBAGAI PENGAWAS MINUM OBAT DAN EFIKASI DIRI PENDERITA TUBERKOLOSIS DI BKPM SEMARANG - Hendiani, Nurlita; Sakti, Hastaning; Widiyanti, Costrie Ganes (Jurnal Psikologi, 2013)
The purpose of this study was to determine the relationship between perceived family support as a PMO and self efficacy of TB patients in BKPM Semarang Region. Perceived family support as PMO is an appraisal of TB patients about her interactions with the family that runs the PMO's role to give motivation in order to achieve healing. Self-efficacy is belief the ability to organize and manage certain action to attain a cure. The population in this study were TB patients in BKPM Semarang Region. Quantitative study with 44 TB patients were obtained through purposive sampling technique. Data collection in this study is Perceived Family Support as PMO Scale (22 aitem Î± = 0.906) and the Self-Efficacy Scale (20 aitem Î± = 0.932), which has been tested on 30 patients with TB in the BKPM Semarang Region. In data evaluation, simple analysis regresion were used. The results of this study indicate correlation value 0.550 and p = 0.000 (p<0.05). There were positive and significant correlation between perceived family support as a PMO and self efficacy. Patients who had positive perception of family support as a PMO had higher self-efficacy scores.